Carbon cycling and mass extinctions: the Permo-Triassic of the Arabian Margin - Clarkson, Matthew O. (The University of Edinburgh, 2014)
The end-Permian extinction at 252 Ma is widely regarded as the most severe of the Phanerozoic mass-extinctions and enabled the evolution of the modern carbon cycle and ecosystem structure. The cause of the extinction is still debated but the synergistic pressures of global climate change, such as anoxia and ocean acidification, were clearly important. The extinction occurred in two phases and is marked by a uniquely protracted recovery period of ~ 5 Myrs where diversity fails to reach pre-extinction levels until the Middle Triassic. This period is characterized by an unstable global carbon cycle, secondary extinctions, reef, chert and coal gaps, and changes in the carbonate factory from reef to microbial and abiotic dominated deposition. This thesis focuses on using geochemical data from the Arabian Margin to investigate the carbon cycle record and the links between kill mechanisms and carbon cycle dynamics. A new record of carbon cycling is presented for the Tethys in the form of a carbon isotope record for the entire Early Triassic from the Musandam Peninsula, United Arab Emirates (UAE). The Musandam carbon isotope record can be broadly correlated with global isotopic events but also resolves additional secondary excursions. These new short-lived events are probably related to the occurrence of the more widely recognized Early Triassic excursions, and may represent fluctuations in the driving mechanisms superimposed on the continued instability of the global carbon cycle in the aftermath of the end-Permian extinction. To unravel palaeo-depositional redox conditions this work utilizes geochemical proxies based on Fe systematics (Fe-speciation). To date, however, these proxies have only been calibrated in relation to modern and ancient siliciclastic marine sediments. This clearly limits the use of the Fe-speciation proxy, particularly in relation to carbonate-rich sediments and rocks. This thesis explores the use of Fe-speciation in carbonates using compiled literature and new data from modern oxic and anoxic ...